Temporal relationship between hepatitis B virus enhancer II/basal core promoter sequence variation and risk of hepatocellular carcinoma. Issue 1 (14th May 2007) - Chou, Y-C; Yu, M-W; Wu, C-F; Yang, S-Y; Lin, C-L; Liu, C-J; Shih, W-L; Chen, P-J; Liaw, Y-F; Chen, C-J
Abstract : Background and aims: To investigate the temporal relationship between sequence variation in the enhancer II (EnhII), basal core promoter (BCP), and precore regions of hepatitis B virus (HBV) and the risk of hepatocellular carcinoma (HCC), we conducted a nested case–control study within a cohort of 4841 male HBV carriers who were recruited during the period 1988–1992. Methods: The HBV DNA sequence was determined in baseline blood samples taken from 132 incident cases and 204 controls. Base exchanges during follow-up in 71 cases were compared with 81 controls with samples taken during a similar length of follow-up. Results: Nine single nucleotide polymorphisms in the EnhII/BCP regions (six of which were genotype C HBV related) were associated with subsequent risk of HCC. The strength of these associations decreased as the lag time between baseline measurement and diagnosis increased over 3 years. However, an increased disease risk in subjects with BCP double variants (mostly T1762/A1764) or genotype C HBV-related variants was evident 9 years or more before diagnosis. The BCP double variants (odds ratio, 1.92 (95% confidence interval, 1.14 to 3.25)) were statistically significantly associated with HCC risk even after adjusting for alanine aminotransferase levels, antibodies against HBV e antigen, HBV genotype, HBV viral load, and other sequence variants. Longitudinal analysis indicated that the increased HCC risks for at-risk sequence variants were attributable to the persistence of these variants. Conclusions: HCC risk is associated with sequence variation in the EnhII/BCP regions of HBV, and persistence of at-risk sequence variants is critical for HCC development.